Simulation of the compression test of the Zr1Nb fuel cladding ring - Vojtěch Smolík; Alžběta Endrychová; Jakub Krejčí (Acta Polytechnica CTU Proceedings)
Fuel cladding is a first protective barrier against the loss of fission products that must withstand extreme conditions, from normal operation to final and interim dry storage. This hostile environment results in mechanical and microstructural damage of cladding caused by different stress levels, temperature, corrosion, hydrogen pick up and other degradation processes further enhanced by radiation. For this reason, the integrity of the cladding is a critical issue. The aim of this work is to simulate a ring compression test to evaluate the stress-strain behavior and hoop fracture properties of a zirconium-based alloy with niobium, which was chosen because it is widely used as fuel cladding in light water nuclear reactors.